Improving Early Childhood Gross Motor Development Through Relay Running Games: A Literature Study: Peningkatan Perkembangan Motorik Kasar Anak Usia Dini Melalui Permainan Lari Estafet: Studi Literatur - fitria sari; Rafita Sari (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
This research is motivated by the low development of gross motor skills of early childhood, this is caused by the gross motor learning of children is still not so optimally implemented so that the gross motor skills of young children is still low, researchers overcome the problem by using relay games. This study aims to improve the gross motor development of early childhood through relay running games. This research uses the literature study method. The results showed that there was an influence on the application of relay games to the development of gross motor skills of early childhood. This is evidenced from the results of analyzing 12 article and 2 books, showing that the application of relay games can improve gross motor skills of young children. Correspondingly, the abilities of children have increased rapidly through the relay game, so that children feel happy and feel comfortable in doing the game. Children are also more eager to learn, and can increase children's confidence. So that through relay games the child becomes a more independent, strong and confident person to appear in public.